Retirement Planning Among Mining Sector Workers in East Kalimantan: The Role of Financial Literacy and Future Time Perspective Through Financial Self-Efficacy - Mawar Ramadani; Mukhibatul Hikmah (Universitas Ibn Khladun Bogor, 2026)
This study was conducted to analyze the influence of financial literacy and future-oriented time perspectives on retirement planning through financial self-efficacy among mining sector workers in East Kalimantan.. The researchers used a quantitative approach with an explanatory survey method. Data were collected by distributing questionnaires in person and online to 170 mining workers in East Kalimantan using a non-probability sampling technique specifically, convenience sampling and were analyzed using a Structural Equation Model based on Partial Least Squares (SEM-PLS). The results indicate that financial literacy has a positive but non-significant effect on retirement planning. Meanwhile, financial literacy significantly enhances financial self-efficacy. Future time perspective positively and significantly influences both retirement planning and financial self-efficacy. Furthermore, financial self-efficacy positively and significantly influences retirement planning. However, financial self-efficacy does not mediate the relationship between financial literacy on retirement planning, whereas financial self-efficacy mediates the effect of future time perspective and retirement planning. These results imply that possessing financial knowledge alone does not insufficient to directly drive retirement planning behavior without a future-oriented mindset and an individual’s confidence in managing long-term finances.